Perception of money and economic behavior: a comparative study of the perception of money in indebted people and savers - Descouvieres, C.; Altschwager, C.; Kreither, J.; Canales, M. (Revista de Psicología, 1997)
The central objective of this study was to explore the social representations of money in people in debt and people who save, and to analyze comparatively the meanings involved in each one. This was carried out from the perspective of qualitative methodology, based mainly on conducting in-depth interviews with men and women, savers and debtors between 25 and 40 years old corresponding to consumer groups C1, C2 and C2C3. The analysis of results made it possible to distinguish qualitative differences between the profile of categories of meaning about money, typical of savers, and the profile of the indebted. In summary, the profile of the indebted considers the following categories of meaning. Money: satisfaction, enjoyment, present, integration, possibility, impulsiveness, temptation, a bet on the future, external control, invisible, reward for effort and undervalued. The profile of savers considers money as: means of subsistence, anti-value, useful, reality, restriction, future, security, tranquility, achievement of goals, planning, effort and sacrifice, self-control and privacy. These social representations are closely related to the attitudes that the two segments present towards savings and debt. And additionally, they seem to be determining factors in economic behavior, specifically in the distribution and use that they make of money.